The Rhino in Right Field - DeKeyser, Stacy (New York : Margaret K. McElderry Books, 2018)
In 1948, Nikko Spirakis, twelve, loves baseball but must get past his hard-working immigrant parents--and the rhino in the outfield--to become a batboy for the local minor league team.
Keywords: Baseball -- Juvenile fiction; White rhinoceros -- Juvenile fiction; Friendship -- Juvenile fiction; Family life -- Juvenile fiction -- Wisconsin; Immigrants -- Juvenile fiction; Greek Americans -- Juvenile fiction; Baseball -- Fiction; White rhinoceros -- Fiction; Friendship -- Fiction; Family life -- Fiction -- Wisconsin; Immigrants -- Fiction; Greek Americans -- Fiction; Wisconsin -- Juvenile fiction -- History -- 20th century; Wisconsin -- Fiction -- History -- 20th century